ANALYSIS OF PASSENGER TERMINAL CAPACITY IN ADI SOEMARMO INTERNATIONAL AIRPORT, BOYOLALI, CENTRAL JAVA PROVINCE - , NUR FITRIANA SOFIATI, Prof. Ir. Sigit Priyanto, M. Sc., Ph. D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Airport is an important facility for a region. It is a vital infrastructure which can connected the region to other regions. It can open opportunity of economic welfare. Airport is also a potency which can attract people to come and visit the region. Solo as one of emerging small medium-sized cities located in Central Java Province, is realizing the position of Adi Soemarmo International airport which is near. It is a potency to make the city become connected. The development of the city surrounds will influence the development of the airport. The analysis was carried out using formulas from JICA (Japan International Cooperation Agency) for the airport terminal capacity and IATA (International Air Transport Association) to evaluate the existing passenger terminal facilities. The forecast of the passenger is also examined in order to anticipate the development of the airport. The result shows that domestic terminal capacity according to JICA is 6,725.90 m2 and the existing domestic terminal is 5,916.02 m2. The international terminal based on JICA is 2,586.68 m2 and the existing condition is 4,336.31 m2. According to IATA, for domestic terminal, 8 facilities out of 19 and for international terminal, 14 facilities out of 19 fulfill the IATA requirements. Domestic terminal of Adi Soemarmo airport has already faced the saturated condition in 2013. International terminal of Adi Soemarmo airport will not face the saturated condition until next 20 years.